Case Report: CD19 CAR-T therapy induces dual remission in AML-M2b patient with CNS-PTLD and relapse - Zhang, Yu; Zhu, Haibo; Xiao, Xia; Zhao, Mingfeng (Frontiers in Immunology, 2025)
BackgroundAcute myeloid leukemia (AML)-M2b with t(8;21)(q22;q22)/RUNX1::RUNX1T1 (AML1-ETO) is associated with a high risk of relapse after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Post-transplant lymphoproliferative disorder (PTLD), particularly involving the central nervous system (CNS), confers a poor prognosis. Although CD19 chimeric antigen receptor T-cell (CAR-T) therapy is established in B-cell malignancies, its application in acute myeloid leukemia (AML) or CNS-PTLD has rarely been reported.CaseA 24-year-old male with AML-M2b showed persistent RUNX1::RUNX1T1 (AML1-ETO) positivity after allo-HSCT. He developed an extramedullary relapse (presacral mass) at 7 months, followed by CNS-PTLD with limb palsy at 9 months post-HSCT. The disease subsequently progressed to bone marrow relapse (RUNX1::RUNX1T1 94.42%, MRD >5%).InterventionGiven the co-expression of CD19 on both the AML and PTLD cells, the patient was treated with donor-derived CD19 CAR-T cells. He experienced manageable grade 1 cytokine release syndrome (CRS) and grade 3 Immune Effector Cell-Associated Neurotoxicity Syndrome (ICANS).OutcomesThe patient achieved a complete response (CR) with negative MRD, disappearance of the fusion gene, reduction of PTLD and extramedullary lesions, and recovery of limb strength.ConclusionThis case demonstrates the efficacy and feasibility of CD19 CAR-T therapy for concomitant post-transplant AML-M2b relapse and CNS-PTLD, leveraging their shared CD19 expression. It provides clinical evidence that targeting a shared antigen with a single CAR-T product can effectively treat heterogeneous malignancies, offering a promising new strategy for such complex cases.